O espaço do romance: questões sobre teoria e historiografia do gênero romanesco a partir da obra de Daniel Defoe - Thiago Panini Primolan (2016)
Taking Daniel Defoes Captain Singleton as a symbol, this thesis undertakes a critique of some of the key concepts of the Modern Novel-theory. At first, a more theoretical discussion examines the spatial-epistemological assumptions supporting concepts as Ian Watt and Sandra Vasconcelos formal realism, and Michael Mckeons dialectical genre. It is claimed that by delimiting a notion of literary genre as a monolithic construction, oriented by a single founding principle, or by assuming the genre as a space constituted only by dualistic relationships, both the scholars theories and concepts prove themselves to be scarcely effective tools for providing a proper framework of analysis for a text so prone to multiplicity of interpretations as Captain Singleton. Remarking the common misconceptions present on the critics reading of Defoes text, and frequently originated from their allegiance to the novels poetics, the work also puts forth, on the form of a proposal, the creation of the novels space, a concept that is part of a theoretical-methodological alternative approach to the notion of the novel as a literary genre.